DOMESTIC AIRCRAFT TICKETS RESERVATION SYSTEM IN PT. VIRGO AIR USING MICROSOFT VISUAL BASIC 6.0 - Leon Spingks E. Naibaho; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2002)
Computer usage in the service industry, especially on ticket reservations, already represents something very important, as a material for storing data using a computer Water PT.Virgo. Computers are no longer regarded as an expenditure or waste of funds but rather as the spearhead of the service business. Because the computer is a tool supporting the success of a business.Therefore this paper tries to provide a design of information systems administration data processing in PT. Virgo Water to continue their activities with a program made reservations and payment with the application of Visual Basic programming language under the control of the administration. With computerized data expected, it can be processed correctly, quickly and accurately.